PTPT-symmetric interference transistor. Issue 1 (December 2018) - Gorbatsevich, Alexander; Krasnikov, Gennadiy; Shubin, Nikolay
Abstract We present a model of the molecular transistor, operation of which is based on the interplay between two physical mechanisms, peculiar to open quantum systems that act in concert: PT P T -symmetry breaking corresponding to coalescence of resonances at the exceptional point of the molecule, connected to the leads, and Fano-Feshbach antiresonance. This switching mechanism can be realised in particular in a special class of molecules with degenerate energy levels, e.g. diradicals, which possess mirror symmetry. At zero gate voltage infinitesimally small interaction of the molecule with the leads breaks the PT P T -symmetry of the system that, however, can be restored by application of the gate voltage preserving the mirror symmetry. PT P T -symmetry broken state at zero gate voltage with minimal transmission corresponds to the "off" state while the PT P T -symmetric state at non-zero gate voltage with maximum transmission – to the "on" state. At zero gate voltage energy of the antiresonance coincides with exceptional point. We construct a model of an all-electrical molecular switch based on such transistors acting as a conventional CMOS inverter and show that essentially lower power consumption and switching energy can be achieved, compared to the CMOS analogues.